High School Biology Learning Media During the Covid-19 Pandemic in Indonesia: Systematic Literature Review - Nur Khafifah Dewi; Much. Fuad Saifuddin (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
The covid-19 pandemic has led to a change in learning from face-to-face to online learning; learning media has an essential role in the online learning process in understanding students to the material studied. This research aims to determine the types and characteristics of high school biological learning media during the covid-19 pandemic. This study is a Systematic Literature Review using Google Scholar and Dimensions databases. Articles that meet the inclusion and exclusion criteria as research data several 29 scientific articles, including international journals, accredited national journals, and not accredited national journals, thesis, and proceedings. The results of this study indicate that there are various types of high school biology learning media during the COVID-19 pandemic, namely visual-based learning media, audio-visual-based learning media, and computer-based learning media. Most often used during the covid-19 pandemic were hypertext media (such as google classroom) and how to use high school biology learning media during the covid-19 pandemic, which were found to be online/offline and installed/not installed. The material biology learning most widely researched is virus and the scope of biology. This study implication shows various learning media biology in senior high school during pandemic covid-19, so other researchers can develop or use other learning media on teaching and learning biology in senior high school.